Investigating the Bias in Orthopaedic Patient-reported Outcome Measures by Mode of Administration: A Meta-analysis. (December 2020) - Acosta, Jonathan; Tang, Peter; Regal, Steven; Akhavan, Sam; Reynolds, Alan; Schorr, Rebecca; Hammarstedt, Jon E.
Abstract : Background: Patient-reported outcome measures (PROMs) are critical and frequently used to assess clinical outcomes to support medical decision-making. Questions/Purpose: The purpose of this meta-analysis was to compare differences in the modes of administration of PROMs within the field of orthopaedics to determine their impact on clinical outcome assessment. Patients and Methods: The PubMed database was used to conduct a review of literature from 1990 to 2018 with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. All articles comparing PROMs for orthopaedic procedures were included and classified by the mode of administration. Each specific survey was standardized to a scale of 0 to 100, and a repeated random effectsmodel meta-analysis was conducted to determine the mean effect of each mode of survey. Results: Eighteen studies were initially included in the study, with 10 ultimately used in the meta-analysis that encompassed 2384 separate patient survey encounters. Six of these studies demonstrated a statistically notable difference in PROM scores by mode of administration. The meta-analysis found that the standardized mean effect size for telephone-based surveys on a 100-point scale was 71.7 (SE 5.0) that was significantly higher (P, 0.0001) than survey scores obtained via online/tech based (65.3 [SE 0.70]) or self-administered/paper surveys (61.2 [SE 0.70]). Conclusions: Overall, this study demonstrated that a documented difference exists in PROM quality depending on the mode of administration. PROM scores obtained via telephone (71.7) are 8.9% higher than scores obtained online (65.3, P, 0.0001), and 13.8% higher than scores obtained via self-administered on paper (61.8, P, 0.0001). Few studies have quantified statistically notable differences between PROM scores based solely on the mode of acquisition in orthopaedic